(untitled) (Research, Society and Development, 2025)
Fixed-time artificial insemination and early pregnancy diagnosis have been widely used in dairy farming as strategies to increase reproductive efficiency and optimize herd productivity. The use of these technologies allows for the control of ovulation timing and rapid pregnancy detection, promoting better organization of livestock management and reducing the calving interval. These advances are particularly important on farms where estrus detection is limited and in production systems seeking more consistent results in the short and medium term. Based on this context, the general objective of this research was to evaluate, through a literature review, the effectiveness of fixed-time artificial insemination and early pregnancy diagnosis in the reproduction of dairy cows, considering factors that directly affect the outcomes of these procedures, such as nutrition, health, and genetics. The adopted methodology was based on a qualitative literature review conducted from 2021 to 2025, using databases such as Lilacs, Capes Journals, Google Scholar, and Scielo. Only studies that focused on dairy cows, were available in full text, and peer-reviewed were included. As a result, it was found that FTAI protocols, when properly applied and combined with effective diagnostic methods such as Doppler ultrasonography and gene expression tests, favor an increase in pregnancy rates, reduce gestational losses, and allow rapid resynchronization of non-pregnant cows. Nutritional, health, and genetic factors were decisive for the success of the analyzed techniques. The research also highlighted the importance of complying with legislation and having qualified technical professionals conduct reproductive programs.